The role of upper limb strength and power in predicting overhead serve performance among u-15 female volleyball athletes - Lestaripriyatmoko, Wahyu Pudji; Romadhoni, Wiga Nurlatifa (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: The low results of the upper serve in volleyball are still a technical problem that is often encountered, especially in the adolescent age group. The ability to serve up is very dependent on the strength and power of the arm muscles which function to produce a strong and directional push. Purpose: The purpose of this study was to determine the contribution of arm muscle strength and arm muscle power to the results of the upper serve on female athletes of the Semarang City Atlas Volleyball Club U-15. Methods: This study uses correlational research. The sample consisted of 15 female athletes aged 15 years who were taken using total sampling technique. The data collection technique uses a 60-second push-up test to measure arm muscle strength, 3 kg medicine ball throw (three attempts, the best results are taken) to measure arm muscle power, and the AAHPER volleyball top serve test (10 attempts) to measure the results of the top serve. Data analysis used descriptive statistics, normality test, correlation, and multiple linear regression. Results: The results of this study indicate that there is a very strong contribution between arm muscle strength, and arm muscle power to the results of the Atlas club female athletes obtained from r square of 0.965 (96.5%). However, when viewed based on the t test (partial) only arm muscle strength contributes 76.88% and is significant to the results of the upper serve with a significance value (Sig.) of 0.025 (p <0.05). Meanwhile, arm muscle power contributed 19.61%, although it was not statistically significant at 0.221 (p> 0.05) to the results of the upper serve